Literature Review: The benefits of occupational health and safety management systems implementation for the safety of workers - Mulyawati, Sita Dewi; Setyaningsih, Yuliani; Denny, Hanifa Maher (Poltekkes Kemenkes Aceh, 2024)
Background: The construction sector is of particular concern with regard to occupational safety and health, given the persistently high incidence of accidents and safety risks. In 2021, there were 234270 cases of work-related accidents, underscoring the urgent need for the implementation of an effective occupational health and safety management system (OHMS) to protect workers and mitigate the risks associated with injuries and accidents.Objectives: This study aims to investigation is to ascertain the advantages of implementing an OHSMS in the construction sector, with a particular emphasis on worker safety.Methods: A literature review in this study employed online databases, including SINTA, Google Scholar, and Garuda. The keywords utilized were